Staging the Resurrection: The Public Theology of Dutch Production and Broadcasting Companies - Klomp, Mirella (International journal of public theology, 2015)
This article looks at the particular ways in which the resurrection of Christ was staged in the public domain during four editions of a popular musical event named The Passion. Since its first edition in 2011, this annual performance on the suffering, death and resurrection of Jesus Christ has become a large media event in Dutch society. The author argues that its organizers—a television production company and two broadcasting companies—in their annual choices on how to shape and stage The Passion, make theological choices. Moreover, she argues that the staged theology of the organizers is to be considered a form of public theology. Pointing out that authority in late-modern network culture is subject of change, the author reveals how the production and broadcasting companies by organizing and actualizing a passion both prove themselves a leading party in the actualization of Christian tradition and turn up as players in the field of public theology.